Budaya Patriarki Dalam Pembungkaman Perempuan Pada Film “ The Stoning Of Soraya M” (Kajian Komunikasi Gender) - Nurul Fatonah; Susi Andrini (Pusat Studi Gender Universitas Jember, 2022)
This study aims to examine the meaning of patriarchal culture in silencing women in the film